European Perceptions and Strategic Responses in the Indo-Pacific - Choi, Yoon Jung (Sejong Instititue, 2024)
This chapter addresses the European approaches and strategies toward the Indo Pacific by outlining the key aims and priorities of the EU (European Union) Indo-Pacific Strategy and of selected EU member states. Firstly, we have a group of countries that influenced the discussions surrounding the formulation of the EU Strategy by releasing their own strategies: France, Germany and the Netherlands. Secondly, we have states like the Czech Republic and Lithuania, which spearheaded their foreign policy plans for the Indo-Pacific in the context of their audits of relations with China. On the supranational level, unlike the US, the EU does not see China only as a threat and its behaviour only as harmful and does not aim to shape the strategic environment to balance Beijing's coercive activities. It views China as an opportunity and a competitor. However, some European countries view China primarily as a revisionist and threatful state using tactics that influence individuals and institutions to favour its narratives of its domestic and foreign policies. Like the EU, South Korea mainly focuses on the prosperity and stability of the Indo-Pacific, particularly the Korean Peninsula. It is thus pertinent to align discussions related to the great power geopolitical rivalry between the US and China, threats coming from North Korea, and non-traditional human security threats related to organised crime, terrorism and cybersecurity. Despite reassurances that ASEAN (Association of Southeast Asian) centrality is to be preserved and supported by all the key players, several minilateral platforms, e.g. the Quad or AUKUS, gained some significance and started to dominate the media narratives. The EU and South Korea can empower the Association and its members to bridge the gap between like-minded Western countries and the ASEAN countries feeling threatened by these latest developments. Enhancing regional security also supports the safety and sustainability of supply chains and trade. This is a long-term process. The actors need to consider possible disadvantages to South Korean companies that are highly engaged with China.